Discovery of a new class of valosine containing protein (VCP/P97) inhibitors for the treatment of colorectal cancer. (15th November 2022) - Wang, Xueyuan; Wen, Tiantian; Miao, Hang; Hu, Wenjiao; Lei, Meng; Zhu, Yongqiang
Graphical abstract: Abstract: Colorectal cancer (CRC) is a common digestive tract malignant tumor and is the third cancer-related death worldwide. Valosine containing protein (VCP/p97) is a member of the AAA ATPase family, plays an important role in the ubiquitin-mediated degradation of misfolded proteins. Studies have shown that p97 is overexpressed in colorectal cancer and is a potential therapeutic target. Herein, a series of novel p97 inhibitors were designed, synthesized and biologically assayed. Based on the enzymatic results, structure–activity relationships (SAR) were discussed in detail. Some potent compounds were further evaluated to inhibit the proliferation of CRC cell lines HCT-116. The results showed that some compounds were active against CRC cell lines with IC50 values of less than 1 μM. Among the screened compounds, compound 10 exhibited good microsomal stabilities, pharmacokinetic properties and displayed strong antiproliferative activity against the HCT-116 cell line (0.4 μM). Furthermore, compound 10 exhibited strong in vivo anticancer efficacy in the human CRC (HCT-116) mouse xenograft model.